The endless search for type specimens; illustrations of eleven spider (Araneae, Mygalomorphae) species described by Eugène Simon - Dupérré, Nadine; Tapia, Elicio (Zootaxa, 2021)
French arachnologist Eugène Simon is considered one of the most prolific arachnologists of all time. Unfortunately, Simon often provided very short descriptions with or without illustrations which makes recognition of his species difficult for subsequent taxonomists. Eugène Simon described 3,789 species of spiders in his career, and most of his type specimens are assumed to be held in the Muséum National d’Histoire Naturelle in Paris, France. We present here the images of eleven Mygalomorphae species described by E. Simon that were never thoroughly illustrated: Cyrtaucheniidae: Fufius albovittatus, F. atramentarius, F. ecuadorensis; Dipluridae: Masteria cavicola, Diplura riveti, and Linothele soricina; Halonoproctidae: Ummidia asperula; Idiopidae: Idiops argus, I. fulvipes, I. opifex and Theraphosidae: Heterothele caudicula.